On Certain Subclasses of Analytic Multivalent Functions Using Generalized Salagean Operator - Adnan Ghazy Alamoush; Maslina Darus (International Journal of Differential Equations)
We introduce and study two subclasses of multivalent functions denoted by Mp,nm,α,β,σ(λ1;λ2) and Np,nm,α,β,σ(μ,δ;γ). Further, by using the method of differential subordination, certain inclusion relations between the two subclasses aforementioned are given. Moreover, several consequences of the main results are also discussed.